Anxiety and Depression Among Chronic Obstructive Pulmonary Disease Patients in A Tertiary Care Hospital, Nepal - Roka, Tara; Aryal, Nirmala; Ghimire, Anjana; Pradhan, Subhadra; Aryal, Krishna Kumar (Journal of Kathmandu Medical College, 2018)
Background: Psychiatric co-morbidities such as anxiety and depression among patients with chronic obstructive pulmonary disease exacerbate the disease, prolong the hospital stay, increase the disease symptoms and deter the quality of life.Objective: To assess the proportion of anxiety or depression among patients with chronic obstructive pulmonary disease in a tertiary care hospital.Methodology: We carried out a cross sectional study interviewing 307 patients from a tertiary care hospital using sequential sampling technique. We used structured questionnaire and included hospital anxiety and depression scale to measure anxiety and depression. We considered a summed score of